Ketercapaian dan Keterkontrolan Sistem Deskriptor Diskrit Linier Positif - Yulia Retno Sari (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2017)
A positive discrete descriptor system has been widely used in modeling economics, engineering, chemistry and others. In this research, we studied the necessary conditions and sufficient conditions for a positive discrete descriptors system is achieved positive and controlled postively. In addition, it is also studied on sufficient terms and conditions which ensure that discrete systems are null controlled. By using linear algebraic method and Inverse Drazin, this research has proved several theorems for discrete descriptors system achieved positive, controlled positively and controlled null. In addition, examples are given as illustrations to reinforce the validity of the proven theorems.